Opportunities and constraints in women's resource security amid climate change: A case study of arid‐living Namibian agro‐pastoralists. Issue 4 (28th June 2021) - Hazel, Ashley; Meeks, Gillian; Bharti, Nita; Jakurama, John; Matundu, Justy; Jones, James Holland
Abstract: Objective: We describe the composition and variation of women's resource strategies in an arid‐living Southern African agro‐pastoralist society to gain insights into adaptation to climate‐change‐induced increased aridity. Methods: Using cross‐sectional data from 210 women collected in 2009 across 28 agro‐pastoralist villages in Kaokoveld Namibia, we conducted principal‐component (PC) analysis of resource variables and constructed profiles of resource strategies from the major PCs. Next, we explored associations between key resource strategies and demographic measures and fitness proxies. Results: The first two PCs accounted for 43% of women's overall resource variation. PC1 reflects women's ability to access market resources via livestock trading, while PC2 captured women's direct food access. We found that market strategies were more common among married women and less common among women who have experienced child mortality. Women with higher subsistence security were more likely to be from the OvaHimba tribe and had a higher risk of gonorrhea exposure. We also qualitatively explored drought‐induced pressure on women's livestock. Finally, we show that sexual networks were attenuated during drought, indicating strain on social support. Conclusions: Our results highlight how agro‐pastoralist women manage critical resources in unpredictable environments, and how resource strategies distribute among the women in our study. Goats as a commodity to obtain critical resources suggests that some women have flexibility during drought when gardens fail and cattle die. However, increased aridity and drought may eventually overwhelm husbandry practices in this region.